India in a changing world : problems, limits, and successes of its foreign policy - Vanaik, Achin (New Delhi : Orient Longman, 1995)
Covers period, 1947 to date.
Includes bibliographical references (p. 135-147).
Keywords: India -- Foreign relations -- 1947-1984.; India -- Foreign relations -- 1984-; 63-92